2019
DOI: 10.1002/mrd.23172
|View full text |Cite
|
Sign up to set email alerts
|

Acentriolar microtubule organization centers and Ran‐mediated microtubule formation pathways are both required in porcine oocytes

Abstract: Mammalian oocytes lack centrioles but can generate bipolar spindles using several different mechanisms. For example, mouse oocytes have acentriolar microtubule organization centers (MTOCs) that contain many components of the centrosome, and which initiate microtubule polymerization. On the contrary, human oocytes lack MTOCs and the Ran‐mediated mechanisms may be responsible for spindle assembly. Complete knowledge of the different mechanisms of spindle assembly is lacking in various mammalian oocytes. In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
(71 reference statements)
0
5
0
Order By: Relevance
“…Centrioles degenerate during early oogenesis, and the pericentriolar material is lost in most species (except for rodents) [91]. Whereas rodent oocytes nucleate spindle microtubules using both acentriolar MTOCs (aMTOCs) and the RanGTP pathway [92][93][94], non-rodent oocytes seem to require the RanGTP pathway only [95,96]. Apart from nucleation factors, spindle assembly involves motor proteins as well as proteins that regulate the growth and stability of microtubules.…”
Section: Open Accessmentioning
confidence: 99%
“…Centrioles degenerate during early oogenesis, and the pericentriolar material is lost in most species (except for rodents) [91]. Whereas rodent oocytes nucleate spindle microtubules using both acentriolar MTOCs (aMTOCs) and the RanGTP pathway [92][93][94], non-rodent oocytes seem to require the RanGTP pathway only [95,96]. Apart from nucleation factors, spindle assembly involves motor proteins as well as proteins that regulate the growth and stability of microtubules.…”
Section: Open Accessmentioning
confidence: 99%
“…In mouse oocytes, the nucleation of microtubules (MTs) relies on the function of acentrioloar microtubule-organizing centers (aMTOCs) [ 15 ], and the depletion of pericentrin (PCNT) from the germinal vesicle breakdown (GVBD) stage, an aMTOCs material, results in disorganized spindle [ 16 ]. However, in porcine oocytes, the aMTOCs are absent before meiosis I, and the nucleation of microtubules in the oocytes is initially mediated by chromatin and Ran GTP gradients [ 17 ]. It is unclear whether PAK1 is required for the assembly of microtubules in porcine oocytes, and its function during the meiotic maturation of porcine oocytes remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to anchoring microtubules, aMTOCs promote microtubule nucleation (30,32,35). However, NUMA neither nucleates microtubules nor interacts with microtubule nucleators, in line with the crucial requirement of the Ran pathway for microtubule nucleation in nonrodent mammalian oocytes (2,36).…”
Section: Discussionmentioning
confidence: 97%
“…The mechanism of spindle pole organization in nonrodent mammalian oocytes, including humans, cows, and pigs, remains unclear. Unlike mouse oocytes, oocytes from these species lack distinct aMTOC foci at their spindle poles (2,36). Although studies of these oocytes have reported localization of a few proteins such as g-tubulin and NUMA (nuclear mitotic apparatus protein) at the spindle poles (2,(37)(38)(39)(40), how these oocytes assemble their spindle poles and control their spindle polarity without centrosomes and aMTOCs remains poorly understood.…”
mentioning
confidence: 99%